The role of digital tools in holiday planning among Polish residents - Weremczuk, Arkadiusz; Suchan, Marta (Turystyka i Rozwój Regionalny, 2023)
This study delves into the influence of digital platforms, including mobile applicationsand online services, on how Polish residents plan and organise their holidays. Specifically, theresearch identifies which applications are most favored and examines the reasons for theirpopularity. A comprehensive survey was used as the primary research tool, the design andimplementation of which is detailed in the following sections of the paper. This analysis exploreskey concepts such as ‘e-tourism’ and offers visual representations of the findings, highlightingcurrent preferences and trends in relation to digital tools in the tourism sector. Finally, thepaper attempts to define and understand the importance of information technologies in themodern development of the e-tourism sector. By integrating the findings of the survey andprevious studies, the work aims to present a holistic perspective on the factors influencing thecontemporary tourism landscape in Poland.